A comparative study of Bachelor of Education and Secondary School Standard Curricula for Geography in Malaysia - Mohmadisa Hashim; Hanifah Mahat; Nasir Nayan; Yazid Saleh (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article examines the extent to which the course structure offered for the Bachelor of Education (B.Ed.) (Geography) honours programme at the Sultan Idris Education University (UPSI) operates in line with the Standards-Based Curriculum for Secondary School (SBCSS) for the subject of geography. Qualitative methods were used to compare the content of geography courses at UPSI and in schools, while qualitative data analysis involved observing, categorizing, scheduling, and incorporating evidence into the initial research proposal. The Standard Document for Curriculum and Assessment (SDCA) of Form 1 to 3 Geography was compared with the 17 courses offered as part of the B.Ed. in Geography by referring to the course's Instructional Plan (IP). ATLAS.ti was used to analyze data from the document. The findings revealed that 14 courses fulfilled the SDCA of Form 1 to 3 SBCSS Geography in secondary schools. However, eight SDCA of Geography SBCSS topics were emphasized to a lesser extent in the existing IP of B.Ed. Geography, namely Position; Sketch Map of Malaysia; Telecommunications in Malaysia; Types and Transportation Development in Asia; Green Technology; Natural Plants in Malaysia; Wildlife in Malaysia; and Recycling. Therefore, a review of the B.Ed. Programme in Geography at UPSI should be undertaken by adding new topics to the existing courses and offering new courses to achieve congruence with the Geography SDCA in schools. The study implies that changes to the curriculum need to be reviewed from time to time so that the existing curriculum is always relevant and meets international standards.